Reading - Wilson, Robert; McCraken, Thomas; Burke, Patrick M.; Cunninghame, George; Morris & Petgrave (Jamaica : [Publisher not identified], 1822)
A plat representing 219 acres of land situate near Lacovia being part of a piece or parcel of land known by the name of Reading and Sally Hall. Lately conveyed by Robert Wilson Esq. to Thomas Mc.Crahen Esq. surveyed 5th August 1822 by Morris & Petgrave, surveyors. Copied 28th August 1839 by Patrick M. Burke for George Cunninghame.
Keywords: Maps; Jamaica -- Maps; St. Elizabeth -- Maps